Implementasi Cyber Public Relations Humas Pemerintah Kabupaten Sumedang melalui Media "WA KEPO" - Raisya Wahyuning Maulida; Evi Novianti; Retasari Dewi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Sumedang Regency Government implements cyber public relations by designing and managing public information using a social media platform called WA KEPO (WhatsApp Kebutuhan Informsi dan Pelayanan Online). This research aims to examine how the Sumedang Regency Government implements cyber public relations. The study employs a qualitative approach with a case study research method. The findings indicate that the Sumedang Regency Government uses WA KEPO as a medium for public information to ensure transparency. Information shared through WA KEPO demonstrates a commitment to transparency. The presence of cyber public relations elements in WA KEPO shows that using WA KEPO as a public information medium represents a form of cyber public relations activity and reflects digital transformation within the government system. The public uses WA KEPO to access information and public services. Although the platform has facilitated access to information, the effectiveness and challenges faced by users when accessing WA KEPO need to be re-evaluated. The Sumedang Regency Government implements cyber public relations through WA KEPO by taking strategic steps to establish the platform and by collaborating with regional organizations (OPDs) and vertical agencies. The choice of WhatsApp is based on its widespread use among people in Indonesia and the convenience and speed it offers in delivering information. This study concludes that the Sumedang Regency Government effectively implements cyber public relations through WA KEPO as an information medium.